Hubungan Pelaksanaan Fungsi Manajemen Kepala Ruang dengan Kinerja Perawat Pelaksana di Ruang Rawat Inap Rumah Sakit DKT Sungai Penuh - Friandi, Riris; Fatriona, Emitra (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT The management function directs nurses in achieving the goals that will be addressed by implementing the nursing process which consists of four elements, namely the planning function, the organizing function, the actuating function, and the controlling function, which are interrelated management cycles. related to each other. Nursing as a profession and nurses as professionals are responsible for providing nursing services according to the competence and authority that they have independently or in collaboration with other members of the health team. It is known that the relationship between the implementation of the management function of the head of the room and the performance of the implementing nurse in the inpatient room of the DKT Hospital. This study uses a descriptive analytic design using a Cross Sectional approach. The sample in this study were 32 respondents and the sampling in this study used the Total Sampling technique. From the results of this study, it is known that there are 16 people (50%) who think that the management function of the head of the room is good, and 16 people (50%) who think it is not good, it is known that the performance of the implementing nurses is good and not good, so the results are the same. The results of this study found that the value of P = 0.000 (P≤0.05) which means that there is a significant relationship between the management function of the head of the room and the performance of the implementing nurse in the inpatient room of DKT Hospital. Keywords: Functions of Head of Room Management, Performance of Implementing Nurses  ABSTRAK Fungsi manajemen mengarahkan perawat dalam mencapai tujuan yang akan ditujukan dengan menerapkan proses keperawatan yang terdiri pada empat elemen yaitu fungsi perencanaan (Planning), fungsi pengorganisasian (Organizing), fungsi pengarahan (Actuating), dan fungsi pengendalian (Controling) yang merupakan siklus manajemen yang saling berkaitan satu samalain (Jakri & Timun, 2019). Keperawatan sebagai profesi dan perawat sebagai tenaga professional bertanggung jawab untuk memberikan pelayanan keperawatan sesuai kompetensi dan kewenangan yang di miliki secara mandiri maupun bekerjasama dengan anggota tim kesehatan lain. Diketahui hubungan pelaksanaan fungsi manajemen kepala ruang dengan kinerja perawat pelaksana di ruang rawat inap Rumah Sakit DKT. Penelitian ini menggunakan desain deskriptif analitik dengan menggunakan pendekatan Cross Sectional. Sampel pada penelitian ini yaitu 32 responden dan pengambilan sampel dalam penelitian ini menggunakan teknik Total Sampling. Dari hasil penelitian ini, diketahui fungsi manajemen kepala ruangan terdapat 16 orang (50%) yang berpendapat baik, dan 16 orang (50%) yang berpendapat kurang baik, diketahui kinerja perawat pelaksana baik dan kurang baik, sehingga didapatkan hasil yang sama. Hasil penelitian ini didapatkan bahwa nilai P=0,000 (P≤0,05) yang berarti terdapat hubungan yang signifikan antara fungsi manajemen kepala ruangan dengan kinerja perawat pelaksana diruang rawat inap Rumah Sakit DKT Kata Kunci: Fungsi Manajemen Kepala Ruangan, Kinerja Perawat Pelaksana